Demographic Determinants of Access to and Usage of Breastfeeding Information among Parents in Mbeya City, Tanzania - Mwantimwa, Kelefa T; Mwaisela, Neema (University of Dar es Salaam Library Journal, 2019)
The main purpose of this study was to examine the influence of demographic characteristics on access to and use of breastfeeding information among parents in Mbeya City, Tanzania. The study mainly deployed a quantitative approach to collect, process and analyze data in order to measure the influence of selected demographic characteristics on access to and use of breastfeeding information. The data collected were analyzed using SPSS to derive descriptive and inferential statistics. The findings suggest that the relationship between access and access and use of formal breastfeeding sources of information is weak (i.e. rho is far from 1) and insignificant (i.e. p> .005) while the relationship between access and use of informal sources of breastfeeding information is strong (i.e. rho is closer to 1) and significant (i.e. p < 0.05). These indicate that informal sources remain potential sources for breastfeeding for breastfeeding information among parents. Further, demographic characteristics (i.e. gender, age, marital status, level of education, and income) have been found to be important predictors to access and usage of breastfeeding information among parents in the study area. In planning for information setting to support accessibility and usability of breastfeeding information, demographic factors have to be taken into considerations.